2004
DOI: 10.1007/s00299-004-0866-z
|View full text |Cite
|
Sign up to set email alerts
|

Powdery mildew pathogens can suppress the chitinase gene expression induced in detached inner epidermis of barley coleoptile

Abstract: Two-step PCR (RT-PCR and nested PCR) was used to detect gene expression in powdery mildew pathogen-infected cells of detached inner epidermis of barley coleoptiles. Cellular contents of infected cells were microscopically suctioned with a micropipette and subjected to PCR. Triosephosphate isomerase and glyceraldehyde-3-phosphate dehydrogenase genes involved in the glycolytic pathway and a stimulus-induced endochitinase gene were targeted, and their expression was determined by detecting cDNAs derived from spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We found that a subtilisin‐chymotrypsin inhibitor (CI‐1B, M0XBS5) was significantly upregulated in C2 (3.57‐fold), whereas another subtilisin‐chymotrypsin inhibitor (CI‐2A, A0A287EI14) was dramatically downregulated in C2 (20‐fold). Chitinases are the hydrolytic enzymes that protect plants against pathogens (Fujita et al., 2004; Toyoda et al., 1991). Two chitinases (D2CVR3 and F2CSS7) were expressed at lower levels in C2.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a subtilisin‐chymotrypsin inhibitor (CI‐1B, M0XBS5) was significantly upregulated in C2 (3.57‐fold), whereas another subtilisin‐chymotrypsin inhibitor (CI‐2A, A0A287EI14) was dramatically downregulated in C2 (20‐fold). Chitinases are the hydrolytic enzymes that protect plants against pathogens (Fujita et al., 2004; Toyoda et al., 1991). Two chitinases (D2CVR3 and F2CSS7) were expressed at lower levels in C2.…”
Section: Discussionmentioning
confidence: 99%
“…To efficiently analyse the interactions, methods are needed to isolate the intracellular content of a single plant cell attacked by a fungal appressorium and/or haustorium. At present, only two techniques are available: micropipette manipulation [39] and laser microdissection [40]. However, these techniques are not widely used because they require considerable skill and specialised equipment.…”
Section: Introductionmentioning
confidence: 99%